Pengaruh Servant Leadership Style dan Komunikasi Interpersonal Terhadap Motivasi Kerja Pegawai Melalui Komitmen Organisasi - Danang Khurniawan; Indra Prasetyo; Woro Utari (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The aims of this study are to describe work motivation, organizational commitment, Servant Leadership Style and interpersonal communication of employees at the Bojonegoro Regency Pusda Office. To analyze the effect of Servant Leadership Style and interpersonal communication on employee motivation through organizational commitment. This type of research is explanatory research and the approach in this research is quantitative. The population is all employees of the Bojonegoro District Pusda Office, totaling 52 people. The sampling technique uses total sampling or saturated sampling, so the sample used is 52 people. In this study, data analysis used Structural Equation Modeling (SEM) and PLS (Partial Least Square) software. The results showed Servant Leadership Style, Interpersonal Communication, Organizational Commitment and Work Motivation in the high category. There is no significant effect between Servant Leadership Style on organizational commitment. There is a significant influence between interpersonal communication on organizational commitment. There is no significant effect between Servant Leadership Style on work motivation. There is a significant influence between interpersonal communication on work motivation. There is a significant influence between organizational commitment on work motivation. There is no significant effect between Servant Leadership Style on work motivation through organizational commitment. There is a significant influence between interpersonal communication on work motivation through organizational commitment.